Effects of two strains of Lactobacillus isolated from the feces of calves after fecal microbiota transplantation on growth performance, immune capacity, and intestinal barrier function of weaned calves - Li, Yuanyuan; Li, Xin; Nie, Cunxi; Wu, Yanyan; Luo, Ruiqing; Chen, Cheng; Niu, Junli; Zhang, Wenju (Frontiers in Microbiology, 2023)
This study was conducted to evaluate effects of Lactobacillus reuteri L81 and Lactobacillus johnsonii L29 supplementation on growth performance, immune status, antioxidant capacity, and intestinal barrier function of weaned calves. To achieve this, 40 calves were randomly assigned to four groups before weaning, control group (Ctrl group), L. reuteri L81 supplementation group (2 g per day per calf), L. johnsonii L29 supplementation group (2 g per day per calf), L. reuteri L81 and L. johnsonii L29 composite group (2 g per day per calf). The results showed that probiotics supplementation increased the average daily weight gain of calves after weaning, reduced weaning diarrhea index (p < 0.05), and increased serum IgA, IgM, and IgG levels (p < 0.05). L. reuteri L81 supplementation significantly decreased IL-6, increased IL-10 and superoxide dismutase (SOD) levels at 21 d after weaning (p < 0.05). Moreover, probiotics supplementation significantly decreased serum endotoxin (ET), diamine oxidase (DAO), and D-lactic acid (D-LA) levels at different time points (p < 0.05). In addition, supplementation with L. reuteri L81 significantly reduced the crypt depth and increased the ratio of villus height to crypt depth (p < 0.05) in the ileum, increased gene expression of tight junction protein ZO-1, Claudin-1 and Occludin in jejunum and ileum mucosa, reduced the gene expression of INF- γ in ileum mucosa and IL-8 in jejunum mucosa, and increased the abundance of beneficial bacteria, including Bifidobacterium, Lactobacillus, Oscillospira, etc. Overall, these results showed that the two strains isolated from cattle feces after low concentration fecal microbiota transplantation improved the growth performance, immune performance, antioxidant capacity, and intestinal barrier function of weaned calves, indicating their potential as supplements to alleviate weaning diarrhea in calves.